1985
DOI: 10.1111/j.1600-0447.1985.tb01262.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of mental disorder in an urban population in central Sweden in relation to social class, marital status and immigration

Abstract: A representative selection of 2,283 persons, 18-65 years old in "former" Stockholm County were examined by psychiatrists in 1970-71. The total non-response was 12%. The 12-month prevalence of mental disorders in relation to social class (I-III), marital status and immigration was estimated. The "psychiatric diagnoses of moderate and severe degree" were significantly more prevalent in social class III (14% and 2.7%) than in I (6.9% and 0.6%) and II (9.8% and 0.9%) and significantly more prevalent among single (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

1985
1985
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 14 publications
0
6
0
1
Order By: Relevance
“…The psychiatric interviews were semistructuredpartly, a psychiatric questionnaire where fixed questions were used and partly unstructured interviewsmade by one of the two participating psychiatrists. An estimate was made of the 12-month prevalence of mental disorders including alcoholism and drug dependence (19,20). The total non-response was 12 %.…”
Section: Methodsmentioning
confidence: 99%
“…The psychiatric interviews were semistructuredpartly, a psychiatric questionnaire where fixed questions were used and partly unstructured interviewsmade by one of the two participating psychiatrists. An estimate was made of the 12-month prevalence of mental disorders including alcoholism and drug dependence (19,20). The total non-response was 12 %.…”
Section: Methodsmentioning
confidence: 99%
“…[130][131][132] Some community-based inquiries have even suggested that immigrants, and indeed refugees, have fewer emotional problems than the native-born. [114][115][116][117][118][119][120][121][122][123][124][125][126][127][128][129][130][131][132][133]134 Although they face a fairly common set of stressors, only a small proportion of immigrants and refugees become psychiatric casualties. This observation strongly suggests that it is not immigration per se, nor even its challenges that creates mental health risk, but rather the interaction among vulnerabilities, stressors, social resources and personal strengths.…”
Section: Genetic Predisposition Plus Environmentmentioning
confidence: 99%
“…The European reports are more diverse, with two from France (35)(36), four from Norway (37-40) (Anderson (39) includes two studies), one from Finland (41), one study on two Polish towns (42), one from Austria (43), one from Iceland (44), one from Denmark (45), and two from Sweden (46)(47)(48)(49)(50).…”
Section: Recent Studies (Since 1950)mentioning
confidence: 99%